Hybrider l’urbain et l’agricole : du lexique au projet de paysage - Axelle Thierry (Projets de Paysage)
This article is the result of doctoral research in landscape architecture. It seeks to decipher the lexical, conceptual and operational developments relating to new configurations linking the urban tissue and agricultural production in urban centres. The first part of the article redefines the context and the issues regarding synergies between the city and agriculture. The second part presents a lexical study of the two emerging concepts of agri-urbanism and agricultural urbanism explaining how these notions contribute to redefining the role of agriculture as a planning tool in urban centres. Their operational and spatial translation is then studied in a series of projects, mainly in the Ile-de-France region, revealing a wide variety of approaches and landscapes. The implementation of such food-producing projects raises several questions about the need to combine urban and agricultural planning tools and to invent new professional practices for negotiating, designing and taking action. From this perspective, the strengthening of approaches in landscape architecture opens up new prospects for federating actors, developing joint projects and thus promoting complementarity between urban and agricultural spaces.